Design and Realization of 2.4 GHz Bowtie Antenna for Ground Penetrating Radar (GPR) - ALtalqi, Fatehi; Elisa, Ulfa; Echchelh, Adil (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2023)
In this research, a microstrip antenna with a bowtie hole was constructed. The proposed antenna is designed and fabricated to operate in the 2.4 GHz frequency band. Arc antennas are a popular choice due to their flat structure, lightweight design, wide bandwidth, and high gain characteristics for GPR applications. The antenna was designed as a microstrip antenna in the size of 58 mm x 69 mm. using an FR4 duplex printed circuit board with a material thickness of 1.6 mm, a dielectric constant of 4.3 and a transverse dielectric loss tangent of 0.02. The design and simulation were performed using CST Studio Suite programming. The results of the simulation and measurements antenna were tested for resonant frequency, return loss, VSWR, bandwidth, impedance, and polarization, and the simulation results were compared. The measurements carried out with a Vector Network Analyzer, showed a return loss of -18, a VSWR of 1.29, a bandwidth of 100 MHz, an impedance of 47ohms, and a high gain of 18 dB at 2.42 GHz. Both the simulation and measurement results demonstrated good agreement, with frequency bands of interest that were very close and stable with high-gain omnidirectional radiation characteristics. Thus, the antenna is well-suited to meet the requirements of GPR applications.